Modelirovanie adaptacionno-prisposobitel'nych reakcij funkcional'nogo sostojanija junych futbolistov-professionalov 15-17 let na osnove integral'nogo monitoringa - Golubev, D. V.; Shchedrina, Yu. A.; Melnikov, D. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents the results of modeling the adaptive reactions of the functional state of the organism of professional footballers 15-17 years in the structure of the microcycle of the preparatory stage of sports training. The study was conducteddaily for four weeks in a state of relative muscle rest and while exercising in the gym and football field. During the experiment, modern technologies were used: GPS CATAPULT (Australia), POLAR (Finland), OMEGA-SPORT (Russia). It is established that the reproduction of models is a tool for predicting the functional capabilities of young football players in the age vector of adaptation, the wave-like tension of the systems providing muscle activity does not fully duplicate the parameters of motor activity. The technology of integrated monitoring of functional state, which allows to quantify functional shifts, physical impact, analyze data and personalize the load, is proposed.